Changes In The Inheritance System Of Pusako Tinggi Assets And Their Impact On The Minangkabau Traditional Inheritance System - Afnaini; M. Syamsudin (Prophetic Law Review, 2022)
This study analyzes changes in the inheritance system of Pusako Tinggi assets and their impact on the Minangakabau customary inheritance system. As empirical legal research, it addresses the changes in the behavior of the Minangkabau indigenous people related to inheritance in Pusako Tinggi assets. To gain a better understanding of the main problem, philosophical, sociological, and case approaches were used. Data were collected by observation, interview, and document study, and they were analyzed in a descriptive-qualitative manner with an inductive conclusion. The results of the study revealed that the following factors caused some changes in the inheritance system of Pusako Tinggi assets in the Minangkabau indigenous people: (1). The influence of the Islamic inheritance system; (2) Registration and Granting of Higher Inheritance Rights; (3) Pusako Tinggi land trade; (4) The weakening power of mamak. Changes in the inheritance system for Pusako Tinggi assets in the Minangkabau people have an impact on: (1) elimination of nephews’ inheritance rights; (2) changes in Mamak’s responsibilities; (3) no addition of pusako tinggi; (4) the development of migratory culture; (5) the use of Pusako Tinggi land for investment.Keywords: inheritance system, Pusako Tinggi, Minangkabau Perubahan Sistem Pewarisan Aset Pusako Tinggi Dan Dampaknya Terhadap Sistem Pewarisan Adat Minangkabau AbstrakKajian ini menganalisis perubahan sistem pewarisan harta benda Pusako Tinggi dan dampaknya terhadap sistem pewarisan adat Minangkabau. Sebagai penelitian hukum empiris, membahas tentang perubahan perilaku masyarakat adat Minangkabau terkait pewarisan harta benda Pusako Tinggi. Untuk mendapatkan pemahaman yang lebih baik tentang masalah utama, pendekatan filosofis, sosiologis, dan kasus digunakan. Data dikumpulkan melalui observasi, wawancara, dan studi dokumen, dan dianalisis secara deskriptif-kualitatif dengan kesimpulan induktif. Hasil penelitian mengungkapkan bahwa faktor-faktor berikut menyebabkan terjadinya perubahan sistem pewarisan harta kekayaan Pusako Tinggi pada masyarakat adat Minangkabau: (1). Pengaruh sistem waris Islam; (2) Pendaftaran dan Pemberian Hak Waris yang Lebih Tinggi; (3) perdagangan tanah Pusako Tinggi; (4) Melemahnya daya mamak. Perubahan sistem pewarisan harta kekayaan Pusako Tinggi pada masyarakat Minangkabau berdampak pada: (1) penghapusan hak waris keponakan; (2) perubahan tanggung jawab Mamak; (3) tidak ada penambahan pusako tinggi; (4) pengembangan budaya migrasi; (5) pemanfaatan tanah Pusako Tinggi untuk investasi.Kata Kunci: sistem pewarisan, Pusako Tinggi, Minangkabau